The elements of style - Strunk, William, 1869-1946.; White, E. B., (Elwyn Brooks), 1899- (New York : Macmillan, 1979)
A manual conveying the principles of plain English style.
Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Professional.
Young Adult
Keywords: English language -- Rhetoric; Rhetoric